1995
DOI: 10.1615/critreveukargeneexpr.v5.i2.10
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Receptor: An Overview

Abstract: The action of androgens in regulating development and growth is mediated by androgen receptor (AR). AR is a member of the steroid hormone receptor superfamily, a class of receptors that function through their ability to regulate the transcription of specific genes. The AR is located in various target tissues, with its levels and activity altered with the onset of various cellular events (e.g., sexual development, malignant transformation). The modulation of AR levels occurs through a number of mechanisms, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
184
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 274 publications
(188 citation statements)
references
References 0 publications
3
184
1
Order By: Relevance
“…Although several studies have revealed how SRs can recognize and interact with their hormone response elements (3,4), the mechanism of how SRs activate target gene expression is not fully understood. Ligand-unbound SRs have been found in the cytosol associated with heat shock proteins (HSPs), including HSP90, HSP70, and HSP56 (5-7).…”
mentioning
confidence: 99%
“…Although several studies have revealed how SRs can recognize and interact with their hormone response elements (3,4), the mechanism of how SRs activate target gene expression is not fully understood. Ligand-unbound SRs have been found in the cytosol associated with heat shock proteins (HSPs), including HSP90, HSP70, and HSP56 (5-7).…”
mentioning
confidence: 99%
“…As in normal prostate cells, androgen action in PCa cells is mediated by a nuclear receptor protein, the human androgen receptor (hAR) that binds androgenic ligands, enters the nucleus and stimulates the transcription of genes having cis-acting androgen response elements within their promoter or regulatory regions (Chang et al, 1995). Androgen depletion, induced by hormonal therapies used to treat advanced PCa patients, transiently suppress disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…29,30). LNCaP cells were transfected with the luciferase reporter constructs, and the Renilla luciferase expression construct was used as a control.…”
Section: Luciferase Reporter Assaysmentioning
confidence: 99%